Treatment patterns and real-world evidence for stage III non-small cell lung cancer in Central and Eastern Europe - Zemanova, Milada (Radiology and oncology (Ljubljana), 2020)
The aim of this project was to collect real-world evidence and describe treatment patterns for stage III non-small cell lung cancer in Central and Eastern Europe. Based on real-world evidence, an expert opinion was developed, and the unmet needs and quality indicators were identified. Patients and methods. A systematic literature search and a multidisciplinary expert panel of 10 physicians from 7 countries used a modified Delphi process to identify quality indicators and unmet needs in patients with stage III non-small cell lung cancer. The profound questionnaire was used to characterize treatment patterns used for stage III non-small cell lung cancer, and a systematic review identified patterns in Central and Eastern Europe. The first questionnaire was completed by a group of medical oncologists, radiation oncologists and pneumologists. The panel of experts attended an in-person meeting to review the results of the questionnaire and to process a second round Delphi. An additional survey was then compiled and completed by the panel. Results. A complete consensus was reached by the panel of experts on a set of evidence-based clinical recommendations. The experience-based questionnaire generated a highly variable map of treatment patterns within the region. A list of unmet needs and barriers to quality care were developed with near-unanimous consent of the panel of experts. Conclusions. The current landscape of diagnostic and therapeutic approaches in Central and Eastern European countries is highly variable. We identified several significant barriers, mainly related to the availability of diagnostic and imaging methods and low rates of chemoradiotherapy with curative intention as initial treatment for unresectable stage III NSCLC.
Keywords: metoda Delphi; nedrobnocelični rak; pljuča; rak (medicina); zdravljenje